Construction of Efficient Multienzyme Cascade Reactions for D-Tagatose Biosynthesis from D-Fructose - Peiyu Miao; Qiang Wang; Kexin Ren; Tongtong Xu; Zigang Zhang; Runxin Hu; Meijuan Xu; Zhiming Rao; Xian Zhang (Fermentation)
D-tagatose is an ideal sucrose substitute with potential applications in food and healthcare. The combined catalysis of polyphosphate kinase (PPK), fructose kinase (FRK), D-tagatose-6-phosphate 3-differential anisomerase (FbaA) and phytase provides a low-cost and convenient pathway for the biosynthesis of D-tagatose from D-fructose; however, there is still a problem of low catalytic efficiency that needs to be solved urgently. Therefore, this study enhanced the biosynthesis of D-tagatose by optimizing the expression levels of PPK, FRK and FbaA in a polycistronic system and knocking out the gene pfka of Escherichia coli. With 30 g/L D-fructose as a substrate, the conversion rate increased to 52%, which was the highest after 24 h. In addition, by constructing a multienzyme self-assembly system with SpyTag and SpyCatcher to improve the whole-cell catalytic ability, the conversion rate was further increased to 75%. Finally, through the fed-batch strategy, the optimal strain Ec-7 produced 68.1 g/L D-tagatose from 100 g/L D-fructose. The multienzyme cascade route reported herein provides an efficient and elegant innovative solution for the generation of D-tagatose.